Paisajes en vilo del Sinofonoceno en la obra del videoartista taiwanés Yuan Goang-Ming - Figliulo, Roberto (El Colegio de México, 2025)
Taiwan is a country built on the edge: politically, because of its relationship with mainland China, and ecologically, for its geographical position in the Pacific. In this paper, I analyse the work of Taiwanese artist Yuan Goang-Ming, whose career has been devoted to his country’s complex situation, always through a personal filter. The context is the “Sinophonecene”, a recent concept that refers to the disaster being wrought by the Sinitic world’s active contribution to the natural disaster of the Anthropocene in recent decades. Yuan’s perspective is simultaneously premonitory and nostalgic. His viewpoint lies at the intersection between past, present, and future.